CLINICAL CASE OF FOOD ANAPHYLAXIS IN A CHILD: DETECTION OF THE MAIN ALLERGENIC TRIGGERS BY MEANS OF MOLECULAR COMPONENT ANALYSIS - Zh. M. Zlobina; M. A. Mokronosova (Педиатрическая фармакология)
Anaphylaxis is an acute potentially life-threatening syndrome; in children, it is usually triggered by food allergy. Virtually any food may serve as a provocative factor for an anaphylactic reaction, which is why timely detection of clinically significant allergens is important for prognosis and prevention of allergies. The article presents case record of a 4-years-old patient with polyvalent sensitization and predisposition to anaphylaxis. Demonstration of this case is aimed at justifying use of molecular allergological diagnostic methods for prognosis and selection of therapeutic tactics. Determination of sensitization profile helps to elaborate the optimal tactics of managing patients with severe allergic reactions. Use of biochips to determine the level of IgE-antibodies to various allergenic molecules helps to recognize and determine the true IgE-mediated sensitization and cross-reactivity in patients with polyvalent allergies, to assess the risk of systemic reactions in the event of a food allergy.